COMPARATIVE STUDY ON PHYSICO-CHEMICAL CHANGES DURING DRY AGING OF BLACK ANGUS AND ROMANIAN SPOTTED BEEF - Maria-Cristina Gliga; Adriana David; Georgiana Cătunescu; Ioana Bodea; Mihai Voevod; Manuel León-Camacho; Maria Tofană (Agricultura)
The Black Angus (BA) beef is considered worldwide as the ideal choice for a wholesome, tasty and at the same time healthy steak. The Romanian spotted (RS) is known as a mixed breed, it is exploited in Romania almost exclusively for milk and rarely for meat. The aim of this study was to compare the physical-chemical changes in BA versus RS after a 21-day dry aging period. The parameters studied were content of fat (%), content of protein (%), content of collagen (%), content of water (%) and collagen-protein ratio. For all the studied compounds, the aged samples present significant changes compared to the initial day. The Pearson correlation highlighted a positive correlation between protein and humidity content and a negative correlation between fat and protein (p<0.05).